2020
DOI: 10.1002/mp.14495
|View full text |Cite
|
Sign up to set email alerts
|

Achievable dose reductions with gonadal shielding for children and adults during abdominal/pelvic radiographic examinations: A Monte Carlo simulation

Abstract: Purpose Recently, medical professionals have reconsidered the practice of routine gonadal shielding for radiographic examinations. The objective of this study was to evaluate the gonadal dose reduction achievable with gonadal shields in the primary beam during abdominal/pelvic radiographic examinations under ideal and non‐ideal shielding placement. Methods CT scans of CIRS anthropomorphic phantoms were used to perform voxelized Monte Carlo simulations of the photon transport during abdominal/pelvic radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the present study, when the bismuth shielding tablets were tested for protecting the front of the body and the front and sides of the body, the dose measured at the two ovaries did not differ considerably, because the dose was mainly incident from the direction of the main X-rays; hence, shielding the front of the body blocks most of the dose, and the scattered dose produced on both sides of the body is relatively small. In pelvic radiology, positioning of the automatic exposure-control (AEC) chambers, pelvic orientation, and gonadal shielding can potentially optimize the radiation dose and the image quality [ 5 , 18 ]. However, those authors concluded that using gonadal shielding can increase the dose area product, leading to repeated radiography exams, especially in female examinations, which raises the question of the actual utility of gonadal shielding in female pelvic radiography.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, when the bismuth shielding tablets were tested for protecting the front of the body and the front and sides of the body, the dose measured at the two ovaries did not differ considerably, because the dose was mainly incident from the direction of the main X-rays; hence, shielding the front of the body blocks most of the dose, and the scattered dose produced on both sides of the body is relatively small. In pelvic radiology, positioning of the automatic exposure-control (AEC) chambers, pelvic orientation, and gonadal shielding can potentially optimize the radiation dose and the image quality [ 5 , 18 ]. However, those authors concluded that using gonadal shielding can increase the dose area product, leading to repeated radiography exams, especially in female examinations, which raises the question of the actual utility of gonadal shielding in female pelvic radiography.…”
Section: Discussionmentioning
confidence: 99%
“…GS reduces received doses to the testes by about 95% and to the ovaries by about 50%. Therefore, GS may be highly effective and play an essential role in decreasing genetic effects (13,14). There are rules and protocols for using GS: GS should be considered when the patient is at or below reproductive age; GS should be inserted when gonads are placed within the radiation field or near the field; and GS should not be an excuse to lead inappropriate patient positioning and poor beam collimation.…”
Section: Introductionmentioning
confidence: 99%
“…GS was first used in 1900 to protect men against sterility (15). In 1950, anxieties about the risk of radiation on sterilityincreased, and GS was again recommended as a protective tool (13). One crucial point is that GS should be applied so that clinical information remains intact (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%